Influence of diet on leukocyte telomere length, markers of inflammation and oxidative stress in individuals with varied glucose tolerance: a Chinese population study. Issue 1 (December 2015) - Zhou, Meicen; Zhu, Lixin; Cui, Xiangli; Feng, Linbo; Zhao, Xuefeng; He, Shuli; Ping, Fan; Li, Wei; Li, Yuxiu
Abstract Objectives To explore influence of carbohydrates/fat proportions, dietary ingredients on telomere length shortening, oxidative stress and inflammation in a Chinese population with different glucose tolerance status. Methods Five hundred and fifty-six Chinese subjects without diabetes history underwent a 75 g, 2 h Oral Glucose Tolerance Test (OGTT). Subjects with diabetes (n  = 159), pre-diabetes (n  = 197), and normal glucose tolerance (n  = 200) were screened. Dietary intakes were evaluated using a semi-quantitative food frequency questionnaire (FFQ). Peripheral blood leukocyte telomere length (LTL) was assessed using a real-time PCR assay. Blood lipid profile, levels of the oxidative stress indicators superoxide dismutase (SOD), glutathione reductase (GR), 8-oxo-2′-deoxyguanosine (8-oxo-dG) and inflammation indicators tumor necrosis factor (TNF-ɑ), interleukine-6 (IL-6) were measured. Levels of HbA1c, plasma glucose, insulin, and C peptide were also determined. Measurements were taken at 0 min, 30 min, 60 min, and 120 min after 75 g OGTT. Insulin sensitivity was evaluated by HOMA-IR. Basal insulin secretion index (HOMA-β), early phase disposition index (DI30 ) and total phase disposition index (DI120 ) indicate insulin levels at different phases of insulin secretion. Results In patients with newly diagnosed diabetes, LTL adjusted by age was longer in HbA1c < 7 % group (log (LTL):1.93 ± 0.25) than in HbA1c ≥ 7 % group (log (LTL):1.82 ± 0.29). LTL was not associated with daily energy intake, diet fat, carbohydrates and protein proportions. Multiple linear regression analysis indicated that legumes, nuts, fish and seaweeds were protective factors for LTL shortening, and sweetened carbonated beverage was a risk factor for LTL shortening ( legumes: β = 0.105, p  = 0.018; nuts: β = 0.110, p  = 0.011; fish: β = 0.118, p  = 0.007; seaweeds: β = 0.116, p  = 0.009; sweetened carbonated beverage: β = −0.120, p  = 0.004 ). Daily energy intake was positively associated with TNF-ɑ, IL-6 (TNF-ɑ:r  = 0.125, p  = 0.006;IL-6:r  = 0.092, p  = 0.04). Fat, carbohydrate proportions were positively associated with TNF-ɑ (fat:r  = 0.119, p  = 0.008 ; carbohydrate:r  = 0.094, p  = 0.043). Seaweeds and dairy intake were negatively associated with 8-oxo-dG (seaweed:r  = −0.496, p  = 0.001;dairy:r  = −0.246, p  = 0.046 ), vegetables and fruits were positively associated with GR ( vegetables:r  = 0.101, p  = 0.034;fruits:r  = 0.125, p  = 0.045). Cereal, meat were positively associated with TNF-ɑ ( cereal:r  = 0.091, p  = 0.048 ; meat:r  = 0.405, p  = 0.009). Conclusion Diabetes patients with better plasma glucose (HbA1c < 7 %) had longer LTL, LTL could reflect plasma glucose status in diabetes patients. LTL were probably not influenced by diet carbohydrates/fat proportions but was associated with diet ingredients. Diet ingredients significantly impacted on markers of inflammation and oxidative stress, which probably had an effect on LTL.